Distributed conflict-free cooperation for multiple connected vehicles at unsignalized intersections. (August 2018) - Xu, Biao; Li, Shengbo Eben; Bian, Yougang; Li, Shen; Ban, Xuegang Jeff; Wang, Jianqiang; Li, Keqiang
Highlights: A CAVs distributed cooperation method for unsignalized intersections is proposed. Rotation projection is used to transform 2D vehicle clusters to 1D virtual platoons. A spanning tree is used to construct the conflict-free geometry topology. The algebraic graph theory is used to model the system dynamics. Abstract: Connected vehicles will change the modes of future transportation management and organization, especially at intersections. In this paper, we propose a distributed conflict-free cooperation method for multiple connected vehicles at unsignalized intersections. We firstly project the approaching vehicles from different traffic movements into a virtual lane and introduce a conflict-free geometry topology considering the conflict relationship of involved vehicles, thus constructing a virtual platoon. Then we present the modeling of communication topology to describe two modes of information transmission between vehicles. Finally, a distributed controller is designed to stabilize the virtual platoon for conflict-free cooperation at intersections. Numerical simulations validate the effectiveness of this method.